2019
DOI: 10.1002/aenm.201903146
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Free, Donor–Acceptor‐Type Polymeric Hole‐Transporting Materials for the Perovskite Solar Cells with Power Conversion Efficiencies over 20%

Abstract: The rich molecular design of electron donor (D)–acceptor (A) polymers offers many valuable clues to obtain high‐efficiency hole‐transporting materials (HTMs) for use in perovskite solar cells (PVSCs). The fused aromatic or heteroaromatic units can increase the conjugation of the polymer backbone to facilitate electron delocalization, which increases the rigidity of adjacent units to prevent rotational disorder and lower the reorganization energy, leading to improved carrier mobility and optimized film morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 68 publications
1
62
0
Order By: Relevance
“…1c and d, the main chain structure of PFDTS exhibits better planarity than PTAA, benefiting π–π stacking of the solid phase. 33 Fig. 1e and f show the electrostatic potential surface distribution of PTAA and PFDTS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1c and d, the main chain structure of PFDTS exhibits better planarity than PTAA, benefiting π–π stacking of the solid phase. 33 Fig. 1e and f show the electrostatic potential surface distribution of PTAA and PFDTS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic route for preparing PPEs is shown in Scheme 1, which is quite straightforward comparing with those reported for donor-acceptor type polymer HTMs. [59][60][61][62][63][64][65][66] The synthetic details and characterization data are provided in Supporting Information. Compound 1 was synthesized from the reaction of two commercial raw materials according to our previous work, [67] which can then be easily transferred to compound 2 via a www.advancedsciencenews.com www.advancedscience.com Corey−Fuchs reaction at a good yield of 71%.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, it was demonstrated that the SiO x thin layer and reduced MO x layers appeared between Si and MO x , leading to Fermi level equilibration across the interface [14]. In addition, such advantages of MO x , with high conductivity and the ability to form a smooth pinholefree layer with organic HTLs, enable high efficiencies in PSCs of more than 20% [15,16]. Additionally, the high transparency of MO x permits their application in inverted PSC configurations [17].…”
Section: Introductionmentioning
confidence: 99%